2021
DOI: 10.3233/nre-210182
|View full text |Cite
|
Sign up to set email alerts
|

Concussion symptoms and temporary accommodations using a student-centered return to learn care plan

Abstract: BACKGROUND: Many students return to school after concussion with symptoms but without formal support. OBJECTIVE: To examine concussion symptoms and temporary academic accommodations during school use of a four-week student-centered return to learn (RTL) care plan. METHODS: Five public high schools used the RTL care plan and contributed student-level data after student report of concussion. Data on concussion symptoms, temporary academic accommodations corresponding to reported symptoms, and accommodations prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The third phase starts with half-days or attending school part time before returning to school full time. This process aligns with the Centers for Disease Control and Prevention concussion management guidelines,13 suggesting that students work with school staff to set accommodations without exacerbating symptoms 42 43. These return-to-school guidelines are not strongly evidence based 34.…”
Section: Discussionmentioning
confidence: 98%
“…The third phase starts with half-days or attending school part time before returning to school full time. This process aligns with the Centers for Disease Control and Prevention concussion management guidelines,13 suggesting that students work with school staff to set accommodations without exacerbating symptoms 42 43. These return-to-school guidelines are not strongly evidence based 34.…”
Section: Discussionmentioning
confidence: 98%
“…Accommodations recommended were collected from medical records (n = 10) and accommodations received were reported by students (n = 8). Three studies reported on college students, 43,68,76 5 on high school, 16,64,[77][78][79] 1 on elementary, 80 and 9 on mixed ages. [50][51][52]54,56,57,59,74,81 Most studies reported the percentage of students receiving accommodations, 43,50-52,56,57,59,64,78,80 whereas data was limited about type or length of time of accommodations.…”
Section: Question 2: What Are Student Perspectives On Returning To Le...mentioning
confidence: 99%
“…This review found that students who had their physical and cognitive needs met through supportive environments had better school outcomes, underscoring the positive impact of RTL interventions. 66,77,79 The literature thus far supports that interventions for RTL could improve GPA and school participation after concussion, 66,106,107 but such interventions studies were few, and represented specific student subgroups (high school ages with persistent symptoms), highlighting the need for continued research into intervention models and outcomes across ages.…”
Section: Contributors To Postconcussion Academic Outcomesmentioning
confidence: 99%
“…The evidence identified on RTA protocols comprised six studies: one RCT, 111 one prospective cohort study, 112 one retrospective cohort study, 113 two prospective case series, 23,114 and one retrospective case series. 115 The studies involved RTA protocols in adolescents with acute concussion.…”
Section: Rta Protocolmentioning
confidence: 99%